Cost-Effectiveness of Adjuvant Trastuzumab Therapy for Early Breast Cancer in Asia: A Systematic Review - Abdul Rafar, Noor Razilah; Hong, Yet Hoi; Wu, David Bin-Chia; Othman, Muhamad Faiz; Neoh, Chin Fen (Elsevier, 2019)
Objectives: To systematically review and assess the quality of the economic evidence of adjuvant trastuzumab usage in early breast cancer in Asian countries. Methods: Literature search was performed using 6 electronic databases (PubMed, Scopus, Ovid MEDLINE, EconLit, National Health Service Economic Evaluation Database, and ISI Web of Knowledge). The final search was performed in October 2018. All potential economic studies were then checked for eligibility. The reporting and methodological qualities of each study were independently assessed by 2 authors of this review, using the Consolidated Health Economic Evaluation Reporting Standards, Drummond, and Philips checklists. To compare the different currencies used in these studies, all costs were converted into US dollars (2016). Results: A total of 6 studies were included; most of them were performed from the healthcare provider perspective. The incremental cost-effectiveness ratio for evaluation performed for a lifetime horizon were reported at $8573 and $20 816 per quality-adjusted life-year in 2 studies. The model outcome was generally sensitive to the changes in trastuzumab drug acquisition cost and discount rate, as well as its clinical effectiveness. For the quality assessment, all studies fulfilled more than 50% of the requirements in the Consolidated Health Economic Evaluation Reporting Standards, Drummond, and Philips checklists. Conclusions: Adjuvant trastuzumab therapy is considered a cost-effective option for early breast cancer in Asian countries including China, Iran, Japan, Singapore, and Taiwan. All studies were generally well conducted. Economic evaluations from the societal perspective, with inclusion of indirect and informal care costs, are warranted to facilitate informed decision making among policy makers. © 2019 ISPOR—The professional society for health economics and outcomes research